Structural, optical and electrical properties of tin doped In2O3 thin films prepared by spray ultrasonic - HAMANI, N; ATTAF, A; SAIDI, H; BENNACEUR, K; MESSEI, N (Courrier du Savoir; Vol. 25 (2018): COURRIER DU SAVOIR (Fevrier), 2018)
ABSTRACT Indium tin oxide (ITO) thin films have been prepared by ultrasonic spray pyrolysis technique using different Sn concentrations on a glass substrate at 400°C. X-ray diffraction patterns reveal that all films have polycrystalline cubic structure with preferentially oriented along (400) plane. The films high optical transmittance is improved from 70 % to 80 % in visible region and optical band gap is increased from 3.69 to 3.84 eV with increasing tin concentration. The electrical measurements were performed using four probes technique. The maximum value of conductivity is 813 (Ω.cm) -1 was measured in 8% Sn doped film. KEYWORDS: In 2 O 3 ; Thin films; Sn doping; Ultrasonic spray method.